2022
DOI: 10.1590/1809-4430-eng.agric.v42n2e20210167/2022
|View full text |Cite
|
Sign up to set email alerts
|

Continuous and Impact Cutting Systems for Sugarcane Harvester

Abstract: The quality of the basal cut of sugarcane during harvest can affect the longevity of the crop, and the cutting tool is one of the main causes of damage during harvesting. The aim of this study was to evaluate the performance of two cutting tools: an impact cutting system (ICS) using knives and a continuous cutting system (CCS) using saws. Laboratory tests were carried out to obtain the stalk damage index at different device travel speeds and to determine the invisible losses caused by each cutting system. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…Marques Filho et al [13] showed that various raw material losses depend on the cutting tool. Invisible losses can reach 0.52 and 0.54% of the total harvested.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Marques Filho et al [13] showed that various raw material losses depend on the cutting tool. Invisible losses can reach 0.52 and 0.54% of the total harvested.…”
Section: Resultsmentioning
confidence: 99%
“…Martins and Ruiz [11], evaluating raw material losses in sugarcane crops, found no differences for this parameter as a function of operational speed. Marques Filho et al [13] showed that harvest speed could increase raw material losses. In this study, harvester speeds did not vary significantly.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations